Impact of modified techniques on outcomes of peroral endoscopic myotomy: A narrative review - Nabi, Zaheer; Nageshwar Reddy, D. (Frontiers in Medicine, 2022)
Peroral endoscopic myotomy (POEM) is an established frontline treatment modality for achalasia cardia. Since its initial description, several modifications have been proposed to the technique of POEM. Broadly speaking, these modifications follow the basic principles of submucosal endoscopy, but incorporate variations in the POEM technique, including the difference in the orientation of myotomy (anterior or posterior), length of myotomy (short or long), and thickness of myotomy (selective circular or full thickness). Some of these modifications have been shown to reduce procedural duration without compromising the efficacy of the POEM procedure. More recently, several alterations have been reported that intend to reduce gastroesophageal reflux after POEM. These include preservation of sling fibers during posterior POEM and addition of NOTES fundoplication to the POEM procedure. Although some of the modified techniques have been compared with the conventional techniques in quality trials, randomized studies are awaited for others. The incorporation of some of these modifications will likely make POEM a technically easy and safer modality in near future. This review aims to discuss the current evidence with regard to the impact of modified techniques on the outcome of POEM.